Improving active fire protection systems at Public Office in Kelantan / Nur Eliza Farhan Mohamad Rudin and Adnin Syaza Jaafar - Mohamad Rudin, Nur Eliza Farhan; Jaafar, Adnin Syaza (2020)
In the construction industry, one of the major things that need to consider is fire protection. This is very important and must be taken into account in the fire protection framework to ensure that public office buildings in Malaysia are in a safe state. The aim of this research is to establish the factors in improving active fire protection systems in Public Office. Objective of the research were to (1) identify the requirement of active fire protection in Public Office Building, (2) to assess the compliance of active fire protection systems in Public Office Building and (3) to recommend the factors for improving active fire protection systems in Public Office Building. In order to achieve this objective, there are two method which is quantitative and qualitative are used for this research. The observation and questionnaire circulated from this analysis to the inhabitants of the Public Office around Kelantan. The questionnaires was distributed to 217 number of occupants in the public office building in Kelantan. Based on research, it can be concluded that most of the respondent aware regarding the fire risk when there is no fire protection in the building. Based on the observation conducted, there are fire protection available in the public office building. They are fire extinguisher, heat detector, smoke detector, and fire hose reel, emergency lighting and emergency signage. Last but not least, it is very importance to ensure the maintenance of the fire protection system to keep the fire protection system running well.